Developing a Culture of Privacy A Case Study. - Power, E.M.
In building a culture of privacy, an organization must clearly articulate privacy as an organizational priority; communicate key privacy and security messages; educate across the organization; raise awareness of the importance of registering privacy incidents and breaches; build privacy into the fabric of the organization's activities; and make privacy information and guidance readily accessible. Accomplishing these objectives provides a framework to create or reinforce a privacy culture. In 2003, the province of Ontario, Canada, created the smart systems for health agency (SSHA) to connect healthcare professionals across the province.
Keywords: Health agency; Healthcare professional; Information security; Organizational privacy culture development; Smart system